FINDING A FAIR LAND DISPUTE SETTLEMENT MECHANISM BETWEEN ADAT LAW COMMUNITY VS. INVESTOR - Lestarini, Ratih (UI Scholars Hub, 2016)
Land utilization for investment in local areas raises various land related problems that ends with conflicts within the community. A conflict that occurs, usually begins with the management of communal land “tanah ulayat” within the adat law community environment, and in this case, land utilization that is managed by the third party (investors). The basic problem is the difference of perception and expectations toward the company that exists in the land which is claimed by the community. Both parties have their own claim on the land based on each legal systems, in this situation adat law or local law faced with state law which is used by investors. So far, the Indonesian government has yet to have legal grounds in giving a directions for land dispute/ conflict settlement mechanism. This paper attempts to give an input regarding a land dispute settlement mechanism that can be accepted for all disputing parties. The paper features critical analysis using legal pluralism approach towards related government policies and technical regulations in the ministerial level. These regulations, among others are, Minister of Agrarian Regulation No. 5 of 1999 and Ministry of Agrarian and Spatial Affairs Regulation No. 9 of 2015, also the draft of Law regarding Recognition and Protection of Adat Law Community.